Empowering traumatized students: the effectiveness of compassion training in overcoming the impact of bullying - Sofwan Adiputra; Mujiyati Mujiyati (Konselor, 2021)
The prevalence of bullying in schools is a widespread issue thatnegatively impacts the psychosocial, self-esteem, and emotional well-being of its victim. Therefore, it is imperative to enhance the self-functioning of students. Compassion training is one of the approaches that can help individuals to survive, understand and obtain the positivity in difficult situations. This study employed a quantitative approach with a quasi-experimental studydesign to obtain 50 high-school students in Pringsewu District, Lampung Province, Indonesia. Furthermore, data collectionwas conducted using a self-function scale developed based on Rogers’theory. The datawere analyzed using the independent t-test techniqueto evaluate the feasibility of changing behaviour by comparing conditions. The compassion training model is proven to increase the fully functioning of students thatare victims of bullying. This can be seen from the increasing indicators of their self-assessment functioning. Meanwhile, fully functioning individuals instinctively help others achieve their need for positivity by expressing genuine concern through harmoniousrelationships. These individuals cultivate an open-minded attitude, maintain a strong sense of purpose, and establish trust in themselves and others.